Caracterização funcional da proteína XAC1201 envolvida na patogenicidade de Xanthomonas citri subsp. citri - Vieira, Flávia Campos Freitas [UNESP] (2014)
The ORF XAC1201 of Xanthomonas citri subsp. citri (Xac) encodes a hypothetical protein and when knocked out by transposon insertion leds to changes in the pathogenicity of the bacterium in citrus. The ORF XAC1201 has 819 bp and encodes a protein with a molecular mass of 29.1 kDa. The coding region was cloned into the expression vector pET SUMO and His-SUMO-XAC1201 fusion protein was expressed in Escherichia coli BL21 (DE3) pLysS strain. The best condition for protein expression in soluble form was 28°C and 250 rpm for 4 hours in the presence of 0.2 mM IPTG. Purification was performed by immobilized metal ions affinity chromatography (IMAC) on a Ni2+-Sepharose column and the non-fusion protein was obtained after digestion with SUMO protease and new chromatography on Ni2+-Sepharose column. The final process yield was 3.18% of the total protein, and the protein was obtained highly pure and in the native form. The identity of the purified protein was confirmed by mass spectrometry analysis with sequence coverage above 80%. Enzymatic assays were made to verify phosphohydrolases and histidine kinase activities, however, the results are inconclusive. It is suggested that XAC1201 is a ubiquitous protein and plays an ancestral role, since it is found in several Phyla within the Bacteria Domain. Obtaining this protein in pure, soluble and native form is the first step towards characterization studies of its function. Since this protein is present not only in Xac but has a ubiquitous presence in many other bacterial groups, the understanding of its function is of great interest to many areas